Oil glands in the Neotropical genus Dahlstedtia Malme (Leguminosae, Papilionoideae, Millettieae) - Teixeira,Simone de Pádua (2009)
Dahlstedtia pentaphylla (Taub.) Burkart and D. pinnata (Benth.) Malme belong to the Millettieae tribe and are tropical leguminous trees that produce a strong and unpleasant odour. In the present work, we investigated the distribution, development and histochemistry of foliar and floral secretory cavities that could potentially be related to this odour. The ultrastructure of foliar secretory cavities were also studied and compared with histochemical data. These data were compared with observations recorded for other species of Millettieae in order to gain a phylogenetic and taxonomic perspective. Foliar secretory cavities were only recorded for D. pentaphylla. Floral secretory cavities were present in the calyx, wings and keels in both species; in D. pinnata they also were found in bracteoles and vexillum. Such structures were found to originate through a schizogenous process. Epithelial cells revealed a large amount of flattened smooth endoplasmic reticula, well-developed dictyosomes and vacuoles containing myelin-like structures. Cavity lumen secretion stains strongly for lipids. Features of the secretory cavities studied through ultrastructural and histochemical procedures identify these structures as oil glands. Thus, if the odour produced by such plants has any connection with the accumulation of rotenone, as other species belonging to the "timbó" complex, the lipophilic contents of the secretory cavities of Dahlstedtia species take no part in such odour production. The presence, distribution patterns and frequencies of secretory structures in Dahlstedtia are taxonomically significant and may be utilized as a diagnostic character which justifies the separation of this genus into two species.